Study on utilization of personal protective equipments by paramedical staffs: an institutional study at RIMS, Ranchi - Kiran, Asha; Kumari, Sushma; Kujur, Manisha; Kashyap, Vivek (International Journal Of Community Medicine And Public Health, 2019)
Background: Personal protective equipment (PPE) continues to play an integral role in prevention of transmission of infection in the healthcare setting. The objective of this study is to determine the level of knowledge, attitude and practice of universal precautions for control of infection among health care workers. Methods: Cross sectional study were conducted at Rajendra Institute of Medical Sciences, Ranchi during the period of November 2018 to January 2019. 151 paramedical staffs were included as study population. Sampling method was consecutive sampling. Results: The present study included 151 paramedical staffs, based on our criteria about knowledge of PPEs, 88.7% (134) of participants had the knowledge, while 11.3% (17) did not have. 77% (116) of paramedical staffs received formal training while 23.2% (35) didn’t. 95.68% had the knowledge about PPEs who received training (116), while out of untrained person 65.71% already had knowledge about PPEs which is statistically significant. Departments which always use PPEs are emergency (50%) followed by pathology (16.6%) and Neurosurgery (13.3%) which is statistically significant. Those who frequently use PPEs, 89.6% had knowledge while 10.4% did not have. 85.4% of paramedical staff change gloves between procedures on same patient. Non availabilityof PPEs inhibit maximum percentage of Paramedical staffs 72% towards use of PPEs followed by lack of information and education 12% and uncomfortable PPEs 5%. Conclusions: Proper training should be provided to healthcare workers for universal precaution. Information about universal precaution can be spread in the form of posters in different wards.